Design and empirical evaluation of a web-based road safety learning platform for improving knowledge on safe driving - Reine Denientya; Maya Arlini Puspasari; Ceria Farela Mada Tantrika (Universitas Serang Raya, 2026)
Road traffic injuries remains a serious concern, particularly for young riders, who face a heightened risk of being involved in accidents. Learning can be used to teach people about road safety, yet little is known about how effective online approaches are when they incorporate games, microlearning, and user-friendly design. This study examined RideSafe, a web-based platform that teaches people about road safety through gamified lessons and a simple interface. Thirty-two university students with more than two years of experience took part and were divided into two groups. One group used RideSafe with games and short lessons. The other group used a regular online learning platform. Knowledge was tested before and after the interventions, and participants also rated the usability of each platform. The results showed that both groups showed improved knowledge, indicating that online method can help people increase road safety. However, the group that used RideSafe with games and short lessons achieved greater gains than the comparison one, suggesting that gamified and bite-sized content enhances learning effectiveness. Participants also rated RideSafe as easy to use and reported high satisfaction with its design. These findings indicate that combining games, microlearning, and intuitive design can strengthen online road safety education. RideSafe demonstrates how such learning can be made more engaging and accessible, offering a model for developing more effective road safety platforms. Continued refinement and evaluation of these approaches are recommended.